Profile of Strategic Competence Education for Sustainable Development Based on Gender in Nature Schools - Dina Mardiana; Suhendar; Aa Juhanda; Ridwansyah (Quagga: Jurnal Pendidikan dan Biologi, 2025)
To advance sustainable development, competencies cannot be taught, but students must develop through experience and reflection to acquire action. One of the important competencies to be applied in education is strategic competence. The purpose of this research to determine the strategic competencies of male and female students at nature school. The method used was descriptive quantitative, the research subjects were Fathia Islamic Junior High School students with a total of 42 students. The questionnaire was used to measure strategic competence as many as 15 questions with positive and negative statements consisting of 5 sub-indicators to achieve strategic competence. The results of the study obtained an average of the calculation of the profile strategic competency of the percentage of ESD obtained from male and female students of 82.84% and 85.10% both in the Excellent category. The highest sub-indicator in male students was able to solve problems by 84.13% while female students the highest sub-indicator was able to provide sustainable innovation by 88.54%. This study shows that strategic competence in male and female students is in the excellent category.